PERFORMANCE OF CIVIL PPARATUS IN THE PUBLIC WELFARE SECRETARIAT OF THE SINGKAWANG CITY REGIONAL SECRETARIAT - Fuji Muhammad (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The problem in this study stems from the ASN of the Public Welfare Section not having direct access, so that it affects the implementation of the main tasks and functions. In addition, there is a lack of professional personnel in the field of Public Welfare in carrying out Duties and Functions and ASN has not been able to optimally read the interests of the community to obtain the priority in the field of Public Welfare that is expected. The purpose of the study is to describe and analyze the performance of ASN of the Public Welfare Section of the Regional Secretariat of Singkawang City in carrying out Duties and Functions. This study uses a descriptive research type with a qualitative approach. The results of this study indicate that the Performance of ASN of the Public Welfare Section has not been in accordance with expectations, this can be seen from the aspect of the quality of ASN performance which is not optimal, the level of consistency of program policies is not in accordance with its duties and functions. From the aspect of the quantity of ASN performance, it has not achieved results according to expectations and from the aspect of the time for completing ASN work, it can be seen that the availability of time in implementing program activities is still relatively lacking. As a suggestion or recommendation, namely to realize the quality, quantity and working time of ASN, it is necessary to understand the vision and mission and objectives of the People's Welfare Section, by socializing the vision, mission and objectives of the organization to all existing ASNs, both through staff meetings, discussions and in informal meetings and to increase the quantity of ASN work in carrying out tasks and functions, it is necessary to increase the number of ASNs with the expertise needed to implement program activities in the field of People's Welfare.